User Experience Design: Analyzing Principles and Practices of User Experience (UX) Design for Creating Intuitive, Engaging, and Accessible Interactive Systems (Human-Computer Interaction Perspectives, 2024)
User Experience (UX) design plays a crucial role in creating interactive systems that are intuitive, engaging, and accessible to users. This paper provides a comprehensive analysis of the principles and practices of UX design, focusing on its importance in today's digital landscape. We explore the key principles that guide effective UX design, such as user-centered design, usability, and accessibility. Additionally, we delve into the practical aspects of UX design, including user research, prototyping, and testing methodologies. By understanding these principles and practices, designers and developers can create more user-friendly and impactful interactive systems.